The voice on the radio - Cooney, Caroline B. (New York, N.Y. : Delacorte Press, 1996)
Fifteen-year-old Janie feels devastated when she discovers that her boyfriend has betrayed her and her family through his college radio program
Companion novel to The face on the milk carton and Whatever happened to Janie?
660
Accelerated Reader AR
Keywords: Friendship -- Fiction; Parent and child -- Fiction; Brothers and sisters -- Fiction